Analysis of the Effect of Regional Original Revenue and Balance Funds on Gross Regional Domestic Product in Lombok Barat Regency in 2010-2022 - Nabila Urningsih; Wahyunadi, Wahyunadi; Endang Astuti (Tinta Emas Institute, 2024)
Economic growth can detail many aspects of an economy. The purpose of this study was to analyze the effect of Regional Original Revenue and Balance Funds on Gross Regional Domestic Product in Lombok Barat Regency. This study uses descriptive research with a quantitative approach. The data collection technique used is literature study and documentation. The data used is secondary data from 2010-2022 obtained from the Central Bureau of Statistics and the Regional Financial and Asset Management Agency (BPAKD) of Lombok Barat Regency. The analysis method used in this research is multiple regression analysis with hypothesis testing using the classical assumption test, followed by a partial t test, a simultaneous f test, and a coefficient of determination (R²) test with a significant level of 5%. The results of the econometric criteria test research in this study did not have classical assumption deviations. Based on partial and simultaneous tests, it shows that Regional Original Revenue and Balance Fund have a positive relationship and have a significant effect on Gross Regional Domestic Product in Lombok Barat Regency. As for the coefficient of determination (R²) value of 98% is influenced by the amount of Regional Original Income and Balance Fund while the rest is influenced by other variables outside the model.